EDUKASI VAKSINASI HPV DAN SKRINING IVA SEBAGAI UPAYA PREVENTIF KANKER SERVIKS - Mizan Prihastuti; Laily Mualifah; Berlina Putrianti; Murti Krismiyati; Erma Nur Fauziandari; Rahma Trisnaningsih (LPPM Politeknik Kesehatan Karya Husada Yogyakarta, 2025)
Cervical cancer is one of the leading causes of female mortality in Indonesia, yet public awareness regarding early detection and HPV vaccination remains low, particularly in rural areas. Socio-cultural barriers and a lack of information are the primary obstacles to preventive efforts. This community service activity aims to improve health literacy regarding the importance of HPV vaccination and Visual Inspection with Acetic Acid (VIA) screening at the village level. The method employed was public health education using a persuasive-educative approach through lectures, visual media, and props demonstrations. The target participants consisted of 20 adolescent girls and 25 women of childbearing age. Evaluation was conducted quantitatively through pre-test and post-test scores and qualitatively through observations of participant responses. The results showed a significant increase in knowledge, with the highest improvement in the function and methods of VIA screening at 47%. Prior to the education, participants tended to have misconceptions and fear of medical procedures; however, post-intervention, participant awareness increased positively. The conclusion of this activity is that community-based socialization is effective in shifting the public paradigm from reactive to proactive, as well as eliminating negative stigmas toward early detection of cervical cancer.